NILAI EIGEN MATRIKS QUATERNION - Susi Ekawati (Department of Mathematics, Hasanuddin University, 2019)
AbstrakMenurut Zhang (2007), jika adalah matriks quaternion dengan dan adalah nilai eigen kiri dari , maka . Dalam penelitian ini akan ditunjukkan tiga hal. Pertama, jika adalah matriks quaternion dengan dan adalah nilai eigen kiri dari maka .Kata Kunci : Quaternion, Determinan Cayley, Nilai Eigen Kiri AbstractAccording to Zhang (2007), if is a quaternion matrix with and is the left eigenvalue of , then . In this paper will be shown, if is a quaternion matrix with and is the left eigenvalue of , then .Keywords : Quaternion, Cayley Determinant, Left Eigenvalue